The Influence of Competence, Work Culture, and Work Infrastructure on Investigation Performance Through the Improvement of Human Resource Quality at the Belawan Harbormaster and Main Port Authority Office - Guntur Harry Syahputra; Mesra B; Hernawaty (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of competence, work culture, and work infrastructure on investigative performance, with improving the quality of human resources (HR) as an intervening variable at the Belawan Harbormaster and Main Port Authority Office. The study was conducted at the Belawan Harbormaster and Main Port Authority Office on Jalan Deli, Medan Belawan District, from late June 2025 to August 2025. The study population consisted of 244 employees, and the sample was obtained using the Slovin formula, resulting in 151 respondents. The research method used a quantitative approach and was analyzed using a structural equation model. The results showed that work culture did not significantly influence investigative performance, but significantly influenced the improvement of human resource quality. Competence significantly influenced both investigative performance and human resource quality improvement. Work infrastructure significantly influenced both investigative performance and human resource quality improvement. Furthermore, improving human resource quality proved to be the variable with the most dominant influence on improving investigative performance. Indirectly, work culture, competence, and work infrastructure significantly influenced investigative performance through improving human resource quality, thus all mediation hypotheses were accepted. The research findings confirm that improving human resource quality is a key determinant in optimizing investigative performance, which can be strengthened through adequate technical competency, a conducive work culture, and adequate work infrastructure. This research provides practical implications: maritime investigation organizations need to prioritize human resource development as a primary strategy for improving investigative performance effectiveness.